Influence of lean–green practices on organizational sustainable performance - Kovilage, Manori Pathmalatha (University of Economics Ho Chi Minh City, 2023)
Purpose The key objectives of this study were to investigate the interactions among the lean, green management practices and organizational sustainable performance measures and explore the possibility of simultaneous implementation of these concepts for improving the organizational sustainable performance. Design/methodology/approach Using the interpretive structural modeling (ISM) technique, the interactions among the lean, green practices and organizational sustainable performance measures were established. A focus group which consisted of purposively selected 15 experts was utilized in the primary data collection. Findings In Sri Lankan context, water and material consumption reduction, energy efficiency, water pollution and greenhouse gas reduction were identified as the dominant green practices, while pull production, lot size reduction, continuous improvement, preventive maintenance, employee involvement and cycle time reduction were the dominant lean practices. Inventory level, profitability, quality, cost, employee satisfaction, customer satisfaction, lead time, resources consumption (material, water, energy) and waste generation were determined as the dominant sustainable performance measures. The resulting ISM-based structural model which consisted of eight levels concluded that firstly lean practices influence the green practices and afterward green practices affect the sustainable performance measures. Research limitations/implications The aim of this study was to develop a hypothetical structural model to explain the interactions among the lean, green management practices and organizational sustainable performance measures. But this hypothetical model was not empirically tested in the current study. So further study is required to empirically test the proposed model. Practical implications Currently organizations who practice for sustainable performance engages, lean and green practices separately without understanding on which practices are stared when and how. So, through the findings of this study, organization who desire to improve the sustainable performance are recommended to begin the journey with lean practices and subsequently move in to green and handle both lean and green initiatives through one functional unit. Originality/value The existing literature does not possess a model for explaining the lean–green synergy and organizational sustainable performance and this study successfully fills this gap. Also the study proposes for the practitioners, when and how the lean and green practices should be initiated and implemented for rising the sustainable performance of an organization.